Type of temperament as a factor of temporary adaptation of athletes of the highest achievements during trans-meridional movements to other environmental conditions - Anatoly A. Kirichuk; Dmitry M. Maksimov; Tatyana V. Bashkireva (RUDN Journal of Ecology and Life Safety)
At the present stage of preparation of athletes of the highest achievements for participation in international competitions it is necessary to know the influence of mental properties on the efficiency of temporary adaptation in the conditions of overcoming several time zones to other environmental conditions. The state of the organism was recorded at rest according to the heart rate variability during a 5-minute measurement using the hardware-statistical complex ‘Varicard’. On the example of elite sportsmen parachutists it was revealed that stable properties of men's temperament protect from the negative impact of stressors, influencing their assessment of the environment. Women are prone to emotional stress and are subject to the negative influence of transmeridional movement, so they need earlier individual and group preparation for competitions than men.